Dynamic of active microbial diversity in rhizosphere sediments of halophytes used for bioremediation of earthen shrimp ponds - Marie Colette; Linda Guentas; Luc Della Patrona; Dominique Ansquer; Nolwenn Callac (Environmental Microbiome, 2023)
Abstract Background In New-Caledonia, at the end of each shrimp production cycle, earthen ponds are drained and dried to enhance microbial decomposition of nutrient-rich waste trapped in the sediment during the rearing. However, excessive ponds drying may not be suitable for the decomposition activities of microorganisms. Halophytes, salt tolerant plants, naturally grow at vicinity of shrimp ponds; due to their specificity, we explored whether halophytes cultivation during the pond drying period may be suitable for pond bioremediation. In addition, plants are closely associated with microorganisms, which may play a significant role in organic matter decomposition and therefore in bioremediation. Thus, in this study we aimed to determine the impact of 3 halophyte species (Suaeda australis, Sarcocornia quinqueflora and Atriplex jubata) on active sediment microbial communities and their implications on organic matter degradation. Results Drying significantly decreased the microbial diversity index compared to those of wet sediment or sediment with halophytes. Microbial profiles varied significantly over time and according to the experimental conditions (wet, dry sediment or sediment with halophyte species). Halophytes species seemed to promote putative microbial metabolism activities in the sediment. Taxa related to nitrogen removal, carbon mineralisation, sulphur reduction and sulphide oxidation were significant biomarkers in sediment harbouring halophytes and may be relevant for bioremediation. Whereas microbial communities of dry sediment were marked by soil limited-moisture taxa with no identification of microbial metabolic functions. Nitrogen reduction in sediments was evidenced in wet sediment and in sediments with halophytes cultures, along with putative microbial denitrification activities. The greatest nitrogen reduction was observed in halophytes culture. Conclusion The efficiency of sediment bioremediation by halophytes appears to be the result of both rhizosphere microbial communities and plant nutrition. Their cultures during the pond drying period may be used as aquaculture diversification by being a sustainable system.